Comment l’ethnographie urbaine s’est imposée aux États-Unis (1920-2000) - Christophe Brochier (Métropoles)
This article seeks to explain the development of urban ethnography and the successful careers of its practitioners, evident in the 1990s but not in the 1920s and 1940s, by examining several factors: the dispersion of University of Chicago students trained in fieldwork, the expansion of the graduate population, the urban revolts of the 1960s, the proliferation of urban research centres, and the growth of anthropologists' interest in 'urban' issues. The article thus provides a better understanding of what is usually imprecisely described as a consequence of the movement of ideas, by following people and institutional developments.